Becoming un-orthodox : stories of ex-Hasidic Jews - Davidman, Lynn, 1955- (Oxford University Press, 2015)
Leaving a religion is not merely a matter of losing or rejecting faith. For many, it involves dramatic changes of everyday routines and personal habits. Davidman bases her analysis on in-depth conversations with forty ex-Hasidic individuals. From these conversations emerge accounts of the great fear, angst, and sense of danger that come of leaving a highly bounded enclave community. Many of those interviewed spoke of feeling marginal in their own communities; of strain in their homes due to death, divorce, or their parents' profound religious differences; experienced sexual, physical, or verba.